Analysis of Climate Change and Future Trends of Precipitation and Temperature in the Karde Dam Basin - Maryam Akbari; Hossein Malekinezhad; mahboobeh hajibigloo (مدیریت بیابان)
Precipitation and temperature are critical indicators for assessing the effects of climate change. Climate change, through alterations in precipitation and temperature patterns, significantly impacts the water cycle and hydrological characteristics of watersheds. In this study, the effects of climate change on temperature and precipitation in the Kardeh Dam Basin were investigated using the CMIP6 series model under three scenarios: optimistic SSP126, intermediate SSP245, and pessimistic SSP585. The study covers the future period from 2021 to 2035, compared to the base period from 1992 to 2014, with downscaling performed using the SDSM model. The results from the SDSM model indicate that, in the future, the greatest increase in precipitation will occur in March during the winter season across all scenarios, while the lowest precipitation will be observed in June, July, August, and September during the spring and summer seasons. Regarding temperature, the highest increase in minimum temperature at the Kardeh Dam and Marshak stations will occur in January during the winter season, while the highest increase in maximum temperature will be observed in July during the summer season. Additionally, the results of the Mann-Kendall test showed that, in the studied scenarios, the values for precipitation, as well as minimum and maximum temperatures, either showed no trend or exhibited fluctuations. The only exceptions were the precipitation values at the Ghosh Bala station in the SSP126 scenario, which exhibited a significant negative trend, and the maximum temperature values at the Kardeh Dam station in the SSP585 scenario, which showed a significant positive trend. Overall, in all scenarios, temperatures are expected to rise in the future period compared to the base period, while precipitation will either increase or decrease depending on the specific month, season, and the mountainous nature of the Kardeh Dam Basin.